Discussion on RB technology and the application in 330MW unit. Issue 4 (February 2020) - Li, Yuanyuan; Yan, Qing; Han, Yingkun; Gao, Song; Yu, Qingbin; Li, Kelei; Liu, Enren; Meng, Xiangrong
Abstract: The RB function can automatically reduce the unit to a specified value after the main auxiliary equipment of the power plant is tripped to reduce the number of unit outages, which is beneficial to the stability of the power system. Based on the experiments of RB test on different types of power units, this paper makes research of RB technical problem, analyzes the characteristics of RB rapid load reduction and RB plan and test results in detail.